The PTS(Ntr) system globally regulates ATP-dependent transporters in Rhizobium leguminosarum. - Prell, J; Mulley, G; Haufe, F; White, J; Williams, A; Karunakaran, R; Downie, J; Poole, P (2012)
Mutation of ptsP encoding EI(Ntr) of the PTS(Ntr) system in Rhizobium leguminosarum strain Rlv3841 caused a pleiotropic phenotype as observed with many bacteria. The mutant formed dry colonies and grew poorly on organic nitrogen or dicarboxylates. Most strikingly the ptsP mutant had low activity of a broad range of ATP-dependent ABC transporters. This lack of activation, which occurred post-translationally, may explain many of the pleiotropic effects. In contrast proton-coupled transport systems were not inhibited in a ptsP mutant. Regulation by PtsP also involves two copies of ptsN that code for EIIA(Ntr) , resulting in a phosphorylation cascade. As in Escherichia coli, the Rlv3841 PTS(Ntr) system also regulates K(+) homeostasis by transcriptional activation of the high-affinity ATP-dependent K(+) transporter KdpABC. This involves direct interaction of a two-component sensor regulator pair KdpDE with unphosphorylated EIIA(Ntr) . Critically, ptsP mutants, which cannot phosphorylate PtsN1 or PtsN2, had a fully activated KdpABC transporter. This is the opposite pattern from that observed with ABC transporters which apparently require phosphorylation of PtsN. These results suggest that ATP-dependent transport might be regulated via PTS(Ntr) responding to the cellular energy charge. ABC transport may be inactivated at low energy charge, conserving ATP for essential processes including K(+) homeostasis.